Recurrent Hemoptysis: A Bronchial Dieulafoy's Lesion in a Pediatric Patient. (May 2021) - Ruthberg, Jeremy S.; Abrol, Anish; Howard, N. Scott
Objective: This paper presents a case of a bronchial Dieulafoy's lesion in a pediatric patient with recurrent hemoptysis. Case report: A 11-year old female presented multiple times with dry cough and hemoptysis to an outside hospital, each time leading to a diagnosis of epistaxis and subsequent discharge. When she arrived to our tertiary center with heavy hemoptysis and no evidence of epistaxis, the patient was urgently taken to the operating room by both the otolaryngology and pediatric pulmonology services. Active bleeding from a Dieulafoy's lesion on the right lower bronchus was found and selective embolization of two tortuous arteries was subsequently performed. The patient was discharged in stable condition without recurrence of hemoptysis over the last two months. Conclusion: While rare, especially in pediatric patients, bronchial Dieulafoy's lesions may cause severe hemoptysis and should be considered in the differential diagnosis when the etiology for hemoptysis is unclear.